Pengaruh Pelayanan Mobile Banking Terhadap Kepuasan Nasabah di Yogyakarta - Maria Kumalasanti; Eni Dwi Susliyanti (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2022)
This study aims to examine the effect of speed, security, accuracy and trust on banking customer satisfaction, either partially or simultaneously. This type of research is a verification research using a quantitative approach. The sample of this research is 100 respondents taken by census method. Data collection techniques using questionnaires and surveys. The data analysis method used multiple linear regression tests, classical assumption tests, hypothesis testing (T test, F test and R test), then the data was processed using the IBM SPSS Statistics 24 application. The results of the F test showed that the four variables were speed, safety, data accuracy. , and trust simultaneously has a significant effect on customer satisfaction in Yogyakarta. The results of the T test show that there is a partial effect of speed, security, accuracy and trust on customer satisfaction in YogyakartaKeywords: Content Marketing, Customer satisfaction